Effect of Smoking on Corneal Endothelium: Doi: 10.36351/pjo.v40i3.1827 - Moaiad Abdullateef Almasoudy; Wisam Hado; Khaldoon Khalil Nile (Pakistan Journal of Ophthalmology, 2024)
Purpose: To determine if smoking has an effect on corneal endothelium. Study Design: Descriptive observational. Place and Duration of Study: Lamar eye center in Kerbala city in Iraq during December, 2023 and January, 2024. Methods: A total of 108 eyes were selected, 54 eyes of smokers and 54 eyes of non-smokers. The smokers included in this study had history of smoking for more than twenty years and they smoke more than 40 cigarettes per day. All the participants were male. Specular microscopy was used to determine four corneal parameters; cell density, hexagonality, coefficient of variation and central corneal thickness. Results: Patients age ranged from 50 to 60 years. Central Corneal Thickness was 515.29±40.62 and 522.37±36.68in smokers and non-smokers respectively with p= 0.32. Coefficient of variation and, Cell Densityand Hexagonal shape parameters were also not statistically different between the two groups (p> 0.05). Conclusion: Smoking does not have a statistically significant effect on the corneal endothelium in terms of cell density, hexagonality, coefficient of variation, and central corneal thickness. However, more studies are needed to provide further evidence.